Speech Acts Used in Covid-19 English and Arabic News Reports: Contrastive Study - Hussein, Aysha; Noori, Baidaa (Al-Adab Journal, 2023)
For the past three years, Covid-19 has been the dominant topic in international media. It has been the central topic of various researches and studies. Accordingly, this study aims at presenting the theoretical background of pragmatics, media discourse, and the relation between the two. In addition, it aims at identifying and uncovering the speech acts used in selected Covid-19 English and Arabic news articles following Searle (1979) taxonomy. The selected articles are published by different local and international digital newspapers, including USA Today, The Guardian, Daily Mail, Almada Newspaper, BAGHDADTODAY.NEWS, and Asharq Al-Awsat Newspaper. The findings of the study prove that speech acts are used more in the English reports than in the Arabic reports. Also, the most frequently used category is assertive speech acts in the two types of data.